Molecular sieves and ultrasound-assisted synthesis of novel 1,3,4-oxadiazole-2-thiones derivatives as potential antifungal agents - Nikalje, Anna Pratima G.; Nimbalkar, Ms Urja D.; Tupe, Santosh; Vazquez, Julio A. Seijas; Tato, Maria Pilar Vazquez (19TH INTERNATIONAL ELECTRONIC CONFERENCE ON SYNTHETIC ORGANIC CHEMISTRY, 2015)
In the category of microorganism, fungi are considered as the special class of microbes responsible for opportunistic pathogenic infections in humans species. Due to the side effects of commercially available antifungal drugs and the emergence of new drug resistant fungal species in the past few years, has forced the researchers to search for novel and efficient antifungal drug molecules. The 1,3,4-oxadiazoles scaffold is associated with diverse biological activities. The multipurpose use of the Mannich bases in pharmaceutical chemistry promote us to prepare a new series of 5-(4-(benzyloxy)substituted phenyl)-3-((phenyl amino)methyl)-1,3,4oxadiazole-2(3H)-thione as antifungal agents. Herein, we report molecular sieves and ultrasound assisted synthesis of novel series of Mannich bases of the 5-substituted 1,3,4-oxadiazole-2-thiones by amino methylation with paraformaldehyde and substituted primary / secondary amines and their evaluation for antifungal activity. The structures of the newly synthesized compounds were determined by IR, NMR and Mass spectral study. The synthesized compounds exhibited interesting moderate to excellent antifungal activity against Candida albicans (NCIM 3557), Candida albicans(NCIM3471), Candida glabrata(NCIM3237), Cryptococcus neoformans (NCIM 3542), Cryptococcus neoformans(NCIM 3378), Aspergillus fumigates(NCIM 902), Aspergillus niger(NCIM 628) using Flucanazole as a standard reference drug. The synthesised compounds 6d, 6f,6g, 6h and 6j exhibited promising antifungal activity as antifungal agents.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular sieves; Ultrasound -assisted

Ultrasound- and molecular sieves-assisted synthesis, molecular docking and antifungal evaluation of 5-(4-(benzyloxy)-substituted phenyl)-3-((phenylamino)methyl)-1,3,4-oxadiazole-2(3H)-thiones - Nimbalkar, Urja D.; Tupe, Santosh G.; Seijas Vazquez, Julio A.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nikalje, Anna Pratima G. (Molecules, 2016)
A novel series of 5-(4-(benzyloxy) substituted phenyl)-3-((phenyl amino) methyl)-1,3,4-oxadiazole-2(3H)-thione Mannich bases 6a-o were synthesized in good yield from the key compound 5-(4-(benzyloxy) phenyl)-1,3,4-oxadiazole-2(3H)-thione by aminomethylation with paraformaldehyde and substituted amines using molecular sieves and sonication as green chemistry tools. The antifungal activity of the new products was evaluated against seven human pathogenic fungal strains, namely, Candida albicans ATCC 24433, Candida albicans ATCC 10231, Candida glabrata NCYC 388, Cryptococcus neoformans ATCC 34664, Cryptococcus neoformans PRL 518, Aspergillus fumigatus NCIM 902 and Aspergillus niger ATCC 10578. The synthesized compounds 6d, 6f, 6g, 6h and 6j exhibited promising antifungal activity against the tested fungal pathogens. In molecular docking studies, derivatives 6c, 6f and 6i showed good binding at the active site of C. albicans cytochrome P450 enzyme lanosterol 14 alpha-demethylase. The in vitro antifungal activity results and docking studies indicated that the synthesized compounds have potential antifungal activity and can be further optimized as privileged scaffolds to design and develop potent antifungal drugs.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular docking; Molecular sieves; Ultrasound

Ultrasound assisted synthesis of 4-(Benzyloxy)-N-(3-chloro-2-(substitutedphenyl)-4-oxoazetidin-1-yl) benzamide as challenging anti-tubercular scaffold - Nimbalkar, Urja D.; Seijas, Julio A.; Borkute, Rachna; Damale, Manoj G.; Sangshetti, Jaiprakash N.; Sarkar, Dhiman; Nikalje, Anna Pratima G. (Molecules, 2018)
A series of ten novel derivatives of 4-(benzyloxy)-N-(3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl) benzamide 6a-j were synthesized in good yield from the key compound 4-(benzyloxy)-N-(substituted benzylidene) benzo hydrazide, called Schiff `s bases 5a-j, by Staudinger reaction ([2 + 2] ketene-imine cycloaddition reaction) with chloro acetyl chloride in the presence of catalyst tri ethylamine and solvent dimethyl formamide (DMF), by using ultra-sonication as one of the green chemistry tools. All the synthesised compounds were evaluated for in vitro anti-tubercular activity against Mycobacterium tuberculosis (MTB) and most of them showed promising activity with an IC50 value of less than 1 mu g/mL. To establish the safety, all the synthesized compounds were further tested for cytotoxicity against the human cancer cell line HeLa and all 6a-j compounds were found to be non-cytotoxic in nature. The molecular docking study was carried out with essential enzyme InhA (FabI/ENR) of Mycobacterium responsible for cell wall synthesis which suggests that 6a and 6e are the most active derivatives of the series. The theoretical evaluation of cell permeability based on Lipinski's rule of five has helped to rationalize the biological results and hence the synthesized azetidinone derivatives 6a-j were also analyzed for physicochemical evaluation that is, absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties and the results showed that all the derivatives could comply with essential features required for a potential lead in the anti-tubercular drug discovery process.
Keywords: ADMET study; anti-tubercular screening; azetidinone; cytotoxicity study; green chemistry; Molecular docking; ultra-sonication